The Emerging Role of the Serine Incorporator Protein Family in Regulating Viral Infection - Xu, Shaofen; Zheng, Zhichao; Pathak, Janak L.; Cheng, Haoyu; Zhou, Ziliang; Chen, Yanping; Wu, Qiuyu; Wang, Lijing; Zeng, Mingtao; Wu, Lihong (Frontiers in Cell and Developmental Biology, 2022)
Serine incorporator (SERINC) proteins, including five members 1-5, are carrier proteins that incorporate the polar amino acid serine into membranes to facilitate the synthesis of phosphatidylserine and sphingolipids, and are involved in the progression of several diseases. SERINC genes are also differentially expressed in tumors. Abnormal expression of SERINC proteins occurs in human cancers of the breast, lung, colon, liver, lung, and various glands, as well as in mouse testis. SERINC proteins also affect cleft lip and palate and nerve-related diseases, such as seizure Parkinsonism and borderline personality. SERINC proteins have garnered significant interest as retroviral factors, spurring efforts to define their function and elucidate the mechanisms through which they operate when associated with viruses. Human SERINC5 and SERINC3 have been found to possess antiretroviral activity for human immunodeficiency virus (HIV), COVID-19, murine leukemia virus (MLV), and equine infectious anemia virus (EIAV), and studies have also shown that SERINC5 inhibits DNA virus hepatitis B virus (HBV). Furthermore, the crystal structure and critical residues of SERINC5 against HIV has been revealed. In this review, we discuss the most prevalent mechanisms by which SERINC3 and SERINC5 antagonize viruses and focus on the potential for therapeutic applications of SERINC5/3 in HIV.